Carbon Conversion and Energy Consumption Analysis Carbonization of Coconut Shell at High Temperature - Diana Silvia Rahma Wardhani; Kirana Aurelia Salshabila; Ardika Nurmawati; Wiliandi Saputro; Erwan Adi Saputro (Nusantara Science and Technology Proceedings, 2023)
Carbon/charcoal is a chemical element with the symbol C. Coconut shell can be changed to carbon using a carbonization process. The carbonization process is the process of changing the original law material into black carbon through combustion in a closed space with limited air. Temperature and time carbonization are very influential in the carbonization process. This experiment aims to observe the effect of the duration of the carbonization process on the amount (yield) of coconut shell charcoal obtained by using mass balance analysis. In this experiment, the coconut shell was made into carbon with a carbonization process using a muffle furnace with a temperature of 400? for 1 hour and 2 hours. The result showed that 200 grams of dry coconut shell carbonized with 1 hour produced 49.45 grams of coconut shell, while carbonized with 2 hours produced 48.69 grams of carbon.